استراتيجيات مهارة القراءة في تعلم اللغة العربية لدى طلبة المدرسة الثانوية الدينية الخيرية بكوالا نرانج،قدح دار الأمان - Noraini Azian Azmi (Penerbit USIM, 2024)
International Language and Education Conference 2021 (iLEC’21) e-PROCEEDINGS “Language and Education : New Norms” 2nd & 3rd November 2021 Organized by : Faculty of Major Language Studies (FPBU), USIM. Editor: Azalia Zaharuddin, Suhaili A. Jalil, Kirembwe Rashid Abdul Hameed, Wan Azura Wan Ahmad.